An arranged marriage eaudiobook - Beverley, Jo (Company of Rogues, 2003)
New York Times best-selling author Jo Beverley has been hailed as "arguably today's most skillful writer of intelligent historical romance" by Publishers Weekly. An Arranged Marriage won the National Readers Choice Award and the Romantic Times Award for Best Regency novel. When her vile brother's wicked scheming ruins her reputation, Eleanor Chivenham is forced into a marriage of convenience. Yet there is much more to her new husband than meets the eye, and soon her heart is filled with unexpected desires.